2011
DOI: 10.1182/blood-2011-05-356238
|View full text |Cite
|
Sign up to set email alerts
|

Donor immunization with WT1 peptide augments antileukemic activity after MHC-matched bone marrow transplantation

Abstract: The curative potential of MHC-matched allogeneic bone marrow transplantation (BMT) is in part because of immunologic graft-versus-tumor (GvT) reactions mediated by donor T cells that recognize host minor histocompatibility antigens. Immunization with leukemia-associated antigens, such as Wilms Tumor 1 (WT1) peptides, induces a T-cell population that is tumor antigen specific. We determined whether allogeneic BMT combined with immunotherapy using WT1 peptide vaccination of donors induced more potent antitumor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Donor CD4 + T cells may contribute to the expansion of plasmablasts and LLPCs, as is the case with the WT1-peptide immunization model. 12 The clinical findings that anti-RP155 Abs have been observed in systemic sclerosis but not in SLE 13 also support the hypothesis that the auto-Abs were derived from donor cells and not patient cells. However, the presence of auto-Ab against RNP70 could not be explained by this hypothesis.…”
supporting
confidence: 63%
“…Donor CD4 + T cells may contribute to the expansion of plasmablasts and LLPCs, as is the case with the WT1-peptide immunization model. 12 The clinical findings that anti-RP155 Abs have been observed in systemic sclerosis but not in SLE 13 also support the hypothesis that the auto-Abs were derived from donor cells and not patient cells. However, the presence of auto-Ab against RNP70 could not be explained by this hypothesis.…”
supporting
confidence: 63%
“…41 Developing methods to immunize the donor immune cell inoculum to tumor antigens, such as WT1 in AML/MDS or complementarity-determining region-3 in B-cell malignancies, may further boost GVT activity. [42][43][44] Finally, our group recently showed that an anti-CD117 (c-KIT) antibody can deplete MDS hematopoietic stem cells and restore normal donor hematopoiesis in xenografted mice. 45 Combining this c-KIT antibody with TLI-ATG conditioning for patients with MDS and AML may deplete stem cell niches, thereby improving donor cell engraftment and chimerism.…”
Section: Discussionmentioning
confidence: 99%
“…Priming donor T-lymphocytes in vitro to increase the frequency of tumor-specific precursors prior to adoptive transfer has been tested in murine models of leukemia ( 47 ), and has proven feasible in patients with multiple myeloma ( 48 ), and lymphoid neoplasms albeit without demonstration of clinical benefit in the latter population ( 49 ).…”
Section: Discussionmentioning
confidence: 99%